ETIOLOGY AND ANTIMICROBIAL PATTERNS OF NEONATAL SEPSIS (The Research of Medical Science Review, 2025)
Background: In the world, sepsis is the third leading cause of neonatal mortality, accounting for almost 225,000 newborn deaths annually. Targeted and successful treatment and prevention efforts require information on the microbiological etiology of newborn sepsis and the antibiotic resistance profiles of the agents that cause it. Objective: This study was conducted to determine the etiological agent of neonatal sepsis and their antimicrobial pattern. Materials and Methods: This cross-sectional study was carried out from March 2023 to April 2024 by Pakistan institute of medical sciences Islamabad and Department Of Microbiology, Hazara University Mansehra. A total of 200 blood samples from patients of both gender were taken for this study. Blood culture and antibiotic sensitivity tests were performed for all the enrolled patients by using Kirby-Bauer disc diffusion method. SPSS version 24 was used for data analysis. Results: A total of 200 neonates were enrolled in the current study. There were 70 (35%) male and 130 (65%) female neonates in our study. Amongst 200 samples, 95 (47.5%) were culture positive. Out of 95 positive blood culture, 73 (76.8%) had gram positive organisms and 20 (21.0%) had gram negative organisms; the remaining two (2.1%) tested positive for Candida spp. Coagulase negative staphylococci (n=35) accounted for the majority of gram-positive organism cases, then Staphylococcus aureus (n=25) and Enterococcus (n=7). Klebsiella (n=13) was the most common cause of gram- negative organism cases, followed by E. coli (n=4) and Pseudomonas (n=3). All the isolates in our study showed resistance to Amoxycillin, Cefixime, and Ampicillin. Amikacin and Vancomycin were susceptible against coagulase-negative staphylococci. Amikacin was completely effective against Staphylococcus aureus, while α-hemolytic Streptococcus was susceptible to Vancomycin, Amikacin, Piperacillin, and Tazobactum. All gram-negative organisms were resistant to ampicillin, cefixime, and Amoxycillin, whereas Enterococcus was sensitive to Amikacin and Vancomycin. Conclusion: Our study concludes that gram-negative bacteria are less common than gram-positive bacteria Among Gram-positive bacteria, coagulase-negative Staphylococci was isolated in majority of the cases While in gram negative isolates Klebsiella was commonly observed. Majority of the isolates were resistant to commonly used antibiotics.